Case Report: Multisystem Autoimmune and Overlapping GAD65-Antibody-Associated Neurological Disorders With Beneficial Effect of Epilepsy Surgery and Rituximab Treatment - Dimova, Petia; Minkin, Krassimir (Frontiers in Neurology, 2022)
Glutamic acid decarboxylase (GAD)-antibodies are associated with disabling conditions such as stiff person syndrome, temporal lobe epilepsy (TLE), limbic encephalitis, cerebellar ataxia (CA) and ocular movement disorders, which are usually chronic and difficult to treat. GAD-related TLE has poor response to antiepileptic drugs and immune therapies, and epilepsy surgery is rarely successful. We report on a 47-year-old female with history of migraine, thyreotoxicosis, Bechterew disease, and drug-resistant TLE. Video-electroencephalography recorded frequent seizures with temporo-insular semiology, correlating to left temporal epileptiform activity and left mesio-temporal hyperintensity on magnetic resonance imaging. GAD-autoimmunity was confirmed by extremely high GAD-antibody titers in serum and cerebrospinal fluid. Steroids, immunoglobulins and cyclophosphamide had no effect, and selective left amygdalectomy was performed based on a very restricted hypermetabolism on positron-emission tomography. After transient seizure-freedom significant epilepsy improvement was observed in spite of memory decline. Transient worsening was noted one year later during diabetes mellitus manifestation, and five years later during presentation of progressive CA. Only rituximab treatment led to improvement in neurological dysfunctions. We believe this case illustrates the diversity and overlap of GAD-associated disorders, the need of aggressive immunotherapy trials in severe patients, as well as the possible benefit from epilepsy surgery in some GAD-TLE.